Heinz-Uwe Haus on culture and politics - Haus, Heinz-Uwe, 1942- (Cambridge Scholars Publishing, 2018)
The late 1980s saw the dissolution of the Iron Curtain and the development of democracy in Eastern European countries that had been oppressed by a range of varieties of communist totalitarian regimes. In Germany, this development led to the abolition of the so-called German Democratic Republic (GDR) and the re-unification of Germany. Heinz-Uwe Haus was one of the leading voices of the movement credited with being instrumental in the collapse of communism in the GDR. In addition, as a leading theatre director in GDR times and beyond, his thinking and action have always combined politics and the.